Implementação do protótipo de uma planta automatizada para o controle de esteiras utilizando CLP - Frauzino, Júlio Carlos de Moraes (2017)
To supply the current demand for production, several automated systems are required in industries. This automation is only possible due to a controller that executes the whole process, analyzing the signals received by the sensors and commanding the action of the actuators. The Programmable Logic Controller (PLC) is a device suitable for the industrial use and was the controller used in this work. The Project consists of building a real prototype of an industrial process, based on the ITS-PLC simulation software, from the company RealGames. The system consists of conveyor belts that select boxes according to size. The execution of the work involves: the signal conditioning of the sensors applied in the plant, presenting similar functioning to the virtual ones; control of the employed actuators and programming in the controller's proper language.